Static and Stability Analysis of Shells with Large Displacements and Finite Rotations - Marcinowski, J. (Engineering Transactions, 2015)
The paper deals with large displacements and finite rotations of elastic shells subjected to the action of external loads. The numerical approach to the problem based on the finite element method in displacement formulation is presented. The degenerated finite element originally introduced by AHMAD et al. [1] and subsequently supplemented by MARCINOWSKI [2] was used in this paper. This very element was essentially suitable for shell problems exhibiting small and moderate rotations, but there exists a possibility to apply it also to problems with finite rotations, provided the updated Lagrangian formulation is adopted. Details of such an approach were presented in the paper. Several examples taken from the literature and confirming the correctness of the applied approach were included.